Fuel cell system production cost modeling and analysis. (March 2023) - Kampker, Achim; Heimes, Heiner; Kehrer, Mario; Hagedorn, Sebastian; Reims, Philipp; Kaul, Oliver
Abstract: Fuel cell technology is seen as a promising option for decarbonizing global mobility. The costs of fuel cell systems are currently too high for increasing market penetration. The Chair of Production Engineering of E-Mobility Components at RWTH Aachen University has developed a cost calculation model for Polymer Electrolyte Membrane (PEM) fuel cell systems based on the method of Process Based Cost Modeling (PBCM) and is investigating possibilities for reducing manufacturing costs through economies of scale in production. The aim of this publication is therefore to present the results of cost modeling of PEM fuel cell systems and to derive design areas for technical innovations in terms of cost reduction through economies of scale in production. To this end, technical production parameters with the greatest influence on the cost structure of PEM fuel cell systems are identified and ranked by applying a sensitivity analysis. Finally, this work provides a recommendation for strategic investments and formulates the need for further research to reduce PEM fuel cell system costs by economies of scale.